Effects of green tea extract on serum uric acid and urate clearance in healthy individuals - Jatuworapruk,K. (Lippincott Williams and Wilkins, 2015)
OBJECTIVE: The objective of this study was to investigate the hypouricemic effects of green tea extract (GTE) in healthy individuals. METHODS: This study comprised 1-week control, 2-week interventional, and 1-week follow-up periods. Participants were assigned randomly at the interventional period to consume GTE at 2 (GTE2), 4 (GTE4), or 6 (GTE6) g/d. Levels of serum uric acid (SUA), uric acid clearance, and serum antioxidant power (using trolox equivalent antioxidant capacity assay) were measured at both ends of each study period. RESULTS: Of 30 participants, 11, 11, and 8 received GTE2, GTE4, and GTE6, respectively. After 2 weeks of consumption, the mean SUA level tended to decrease in all groups, with no statistical significance. Serum uric acid reduction was greatest in GTE2 (from 4.81 ± 0.81 mg/dL to 4.64 ± 0.92 mg/dL, 3.53%). Uric acid clearance decreased significantly in GTE2 (from 11.37 ± 6.41 mL/min per 1.73 m to 7.44 ± 2.74 mL/min per 1.73 m, 34.56%, P < 0.05) and GTE4 (from 8.36 ± 3.41 mL/min per 1.73 m to 5.78 ± 2.33 mL/min per 1.73 m, 30.86%, P < 0.05). Serum antioxidant capacity (TEAC) increased significantly in GTE6 (from 32.77 ± 3.39 mg/mL to 35.41 ± 3.17 mg/mL, 8.06%, P < 0.05). There was no significant change in creatinine clearance. Gastrointestinal adverse events were common, but usually mild, with no medical treatment required. CONCLUSIONS: Green tea extract may modestly lower SUA level and decreases uric acid clearance. Green tea extract also significantly elevated serum antioxidant capacity with a positive dosage effect. The effect of GTE on SUA in healthy individuals was short term. The effects of GTE on urate handling in patients with hyperuricemia or gout need to be determined. Copyright © 2014 by Lippincott Williams &Wilkins.